Comprehensive Effects of Creatine Supplementation on Physical Performance, Recovery, and Health Markers Across Diverse Populations - Homza, Michał; Bychowski, Mateusz; Kwaśna, Julia; Załęska, Adrianna; Kaźmierczyk, Izabela; Lenart, Kacper; Górski, Mateusz; Zakrzewska, Natalia; Bednarek, Szymon; Kulicka, Joanna (Quality in Sport, 2024)
Background: Creatine supplementation is well-established for its ergogenic benefits, enhancing physical strength, endurance, recovery, and fatigue management across diverse populations. Research highlights its role in mitigating exercise-induced muscle damage and improving health markers, including oxidative stress, hydration, and body composition. This review synthesizes current evidence on creatine’s comprehensive effects across varied demographics and activity contexts. Methods: This review examined creatine’s effects on performance, recovery, and health markers across athletes, older adults, postmenopausal women, and long COVID patients, analyzing strength, endurance, fatigue, body composition, and biochemical metrics with demographic subgroup analyses. Results: Creatine supplementation improved muscle strength, endurance, and fatigue resistance, especially when combined with resistance training. Benefits included enhanced sprint and jump performance, recovery from muscle damage, and better fatigue management. It also increased lean mass and hydration, reduced oxidative stress, supported bone health, and improved quality of life in clinical populations. Conclusion: Creatine supplementation offers broad benefits for performance, recovery, and health, particularly in athletes, older adults, and clinical populations. Its synergy with resistance training and other supplements underscores its versatility. Future studies should focus on personalized protocols to maximize effectiveness and address individual variability.